(untitled) (Estudios humanísticos. Geografía, historia y arte, 1995)
The author offers a synthesis full of information of the history and development of the book in the Middle Ages in its material appearance as well as in its internal one. This analysis gives the author the opportunity of underlining other aspects of the book, such as its diffusion, social function, course of making, etc.